Pengaruh Kompos Kotoran Ternak Terhadap Sifat Kimia Tanah - Risto Marimba Awang, Ardian; Jawang, Uska (JURNAL AGROPLANT, 2024)
Plant production factors influence the soil media, the ability of the planting media to provide nutrients will increase product yields. Nutrient deficiencies can be supplemented through fertilization. Livestock manure is an organic material that provides the nutrients needed by the soil to improve soil properties The purpose of this study was to determine the effect of livestock manure compost on soil chemistry. The method used in this study was a complete random trial design with six treatments repeated three times. The treatments were P0: control, P1: 10 ton ha-1 of cow dung, P2: 10 ton ha-1 of buffalo manure, P3: 10 ton ha-1 of goat manure, P4: ton ha-1 of horse manure, and P5: 10 ton ha-1 of pig manure. Soil chemistry observed were organic C, total nitrogen, P2O5, K2O, and CEC. The results showed that all fertiliser treatments affected soil chemical properties. The highest mean value of parameters was influenced by composted animal manure from pigs. Based on the data that has been obtained, the highest average nitrogen value is compost treatment from pig manure with a % nitrogen value of 0.96.